Stones into schools : promoting peace with books, not bombs, in Afghanistan and Pakistan - Mortenson, Greg. (New York : Viking, 2009)
In this dramatic first-person narrative, Greg Mortenson picks up where'Three Cups of Tea' left off in 2003, recounting his relentless, ongoing efforts to establish schools for girls in Afghanistan; his extensive work in Azad Kashmir and Pakistan after a massive earthquake hit the region in 2005; and the unique ways he has built relationships with Islamic clerics, militia commanders, and tribal leaders even as he was dodging shootouts with feuding Afghan warlords and surviving an eight-day armed abduction by the Taliban.
The Promise -- The people at the end of the road -- The man with the broken hand -- The year zero -- The sound of peace -- Style is everything -- The seal of the Kirghiz Khan -- Qayamat ('The Apocalypse') -- A dark and distant roar -- No idea what to do -- Farzana's desks -- Sarfraz's promise -- The chance that must be taken -- The School on the Roof of the World -- An E-mail from the American colonel -- The man from the Jalozai refugee camp -- Barnstorming through Badakshan -- A meeting of two warriors -- The point of return -- The last best school -- Investing in girls' education yields high returns -- Key ingredients in successfully building girls' schools -- Take action.
Includes index.
Keywords: Mortenson, Greg -- Anecdotes; Taliban -- History; Girls' schools -- Afghanistan; Girls' schools -- Pakistan; Humanitarian assistance, American -- Afghanistan; Humanitarian assistance, American -- Pakistan; Peace-building -- Afghanistan; Peace-building -- Pakistan